The robust hydraulic system in moso bamboo: Unveiling the spatial distribution of metaxylem vessels - Xu, Haocheng; Tian, Feiyu; She, Yanan; Wang, Shaocong; Su, Na; Xu, Xinwu (Industrial crops and products, 2024)
Effective and robust hydraulic materials with exquisite microchannel are desirable for advanced applications in catalytic/desalination filter, micro reactor, and interfacial evaporator. Bamboo is one of the loftiest “grass” with a height of up to 20 m, mainly attributed to the metaxylem vessels throughout the culm, which transport water and inorganic salts. Here, a novel detection model is constructed for investigating both the axial and radial distribution of vessels within the entire cross-section of bamboo culm based on the You Only Look Once algorithm. The macro characteristics (wall thickness, circumference, and cross-sectional area, etc.) and the micro characteristics (number, distribution density, area, and area proportion of vessels) of each internode were first complete obtained. It’s found that the vessel area proportion consistently enlarges along the axis, offering a compensatory mechanism for the escalating hydraulic resistance with culm height. Furthermore, the radial distribution of vessels’ size increased exponential. Intriguingly, the inflection point of the rate change in vessel area proportion aligned closely with that of the fiber area proportion change, located at one-third the thickness of the culm away from the epidermis. This implies that bamboo, as a highly adaptive plant, intelligently and strategically places fibers with high strength at the epidermis to shield larger-sized vessels, ensuring efficient and robust hydraulic transport. Finally, leveraging the confusion matrix, artificial neural network was employed to investigate the vessel area proportion's predominant positive influence on hydraulic transport performance among all structural characteristics. This relationship serves to clarify the natural hydraulic system in bamboo and provides a valuable reference for the development of innovative technologies in biomimetics and hydraulic engineering. [Display omitted] •An intelligent model realizes the identification of vessels within the entire culm.•Vessel area proportion increases along the axis to compensate hydraulic resistance.•Vessels’ size increases exponentially along the radial distribution.•High-strength fibers at the epidermis shield vessels, ensuring hydraulic transport.•Relationship between structure characteristics and hydraulic transport is explored.